2022
DOI: 10.1038/s41368-022-00175-3
|View full text |Cite
|
Sign up to set email alerts
|

Loss of KDM4B impairs osteogenic differentiation of OMSCs and promotes oral bone aging

Abstract: Aging of craniofacial skeleton significantly impairs the repair and regeneration of trauma-induced bony defects, and complicates dental treatment outcomes. Age-related alveolar bone loss could be attributed to decreased progenitor pool through senescence, imbalance in bone metabolism and bone-fat ratio. Mesenchymal stem cells isolated from oral bones (OMSCs) have distinct lineage propensities and characteristics compared to MSCs from long bones, and are more suited for craniofacial regeneration. However, the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…Senescence-escaped MSCs showed increased H3K9me and enhanced DNA methylation of the senescence-associated p16(INK4a) gene [ 107 ]. Recently discovered epigenetic regulators of both BMSC cell senescence and osteogenic differentiation includes nucleosome assembly protein 1-like 2 (NAP1L2), DNA N6-methyladenine (N6-mA) demethylase Alkbh1, KDM4B, H3K9 demethylases KDM3A and KDM4C, BMI1 [ 5 , 55 , 108 , 109 , 110 , 111 , 112 ]. Loss or gain of functions of these regulators affect BMSC self-renewal, senescence, and osteogenesis.…”
Section: Molecular Mechanisms Of Msc Senescencementioning
confidence: 99%
See 1 more Smart Citation
“…Senescence-escaped MSCs showed increased H3K9me and enhanced DNA methylation of the senescence-associated p16(INK4a) gene [ 107 ]. Recently discovered epigenetic regulators of both BMSC cell senescence and osteogenic differentiation includes nucleosome assembly protein 1-like 2 (NAP1L2), DNA N6-methyladenine (N6-mA) demethylase Alkbh1, KDM4B, H3K9 demethylases KDM3A and KDM4C, BMI1 [ 5 , 55 , 108 , 109 , 110 , 111 , 112 ]. Loss or gain of functions of these regulators affect BMSC self-renewal, senescence, and osteogenesis.…”
Section: Molecular Mechanisms Of Msc Senescencementioning
confidence: 99%
“…Furthermore, the MSC-specific depletion of Kdm4b exacerbated skeletal aging and bone-fat imbalance in aged and OVX mice [ 5 ]. Intriguingly, KDM4B also plays a critical role in mediating and prevention of MSC senescence, while loss of KDM4B with age has been shown to accelerate loss of self-renewal and the premature onset of senescence [ 5 , 112 ]. These implicate the potential epigenetic link between MSC senescence and the bone-fat imbalance in skeletal aging.…”
Section: Role Of Msc Senescence In Age-related Bone Diseasesmentioning
confidence: 99%
“…Furthermore, senescence-associated β -galactosidase (SA- β -gal) staining revealed that KDM4B ablation promoted senescence in OMSCs with elevated CDKN2A and CDKN1A gene expressions in late passages. KDM4B loss promotes adipogenesis and OMSCs aging, which further impairs the bone lipid balance in the mandible ( 162 ). EZH2 enhances the modification of H3K27me3 on the FOXO1 promoter and inhibits its function in activating downstream genes in antioxidant defense.…”
Section: Epigenetic Control Of Mscs In Bone Regenerationmentioning
confidence: 99%
“…17,18 However, under specific pathological conditions, such as an inflammatory microenvironment, an imbalance between bone resorption and bone formation occurs, leading to abnormal bone remodeling. 19,20 Chronic inflammation is one of the most common pathological conditions affecting bone homeostasis. 21 TNF-α, a proinflammatory cytokine within the upper reaction cascade, can induce the inflammatory process.…”
Section: Introductionmentioning
confidence: 99%
“…Coordinated activities of osteoblasts, chondrocytes, and osteoclasts promote the dynamic coupling balance during the bone remodeling process 17,18 . However, under specific pathological conditions, such as an inflammatory microenvironment, an imbalance between bone resorption and bone formation occurs, leading to abnormal bone remodeling 19,20 . Chronic inflammation is one of the most common pathological conditions affecting bone homeostasis 21 .…”
Section: Introductionmentioning
confidence: 99%